Additives for Improving the Fuel Economy of Diesel Engine Systems - Kenji Yamamoto (Japanese Society of Tribologists, 2010)
Due to tightening CO2 emission regulations and increasing fuel prices, fuel economy has become one of the greatest issues facing society today. Although molybdenum dithiocarbamate (MoDTC) is a well-known friction modifier for gasoline engines, it has rarely been applied to a diesel application because of the negative effect soot has on the friction-reducing properties of MoDTC. This study examines which soot properties may influence the friction-reducing attributes of oil containing MoDTC. Fuel consumption tests were also conducted using heavy-duty diesel trucks that met the emission standards of the new long-term Japanese regulations. As a result, a fuel economy improvement of around 2% was observed.